Factors affecting the growth formation of nanostructures and their impact on electrode materials: A systematic review. (October 2022) - Hussain, Iftikhar; Lamiel, Charmaine; Sahoo, Sumanta; Ahmad, Muhammad; Chen, Xi; Javed, Muhammad Sufyan; Qin, Ning; Gu, Shuai; Li, Yuxiang; Nawaz, Tehseen; Ansari, Mohd Zahid; Zhang, Kaili
Abstract: From composites that store energy in batteries and supercapacitors, to tiny particles that enter the human body, nanocomposites are found everywhere. Depending on the applications, nanocomposites with unique and ordered structures may deliver wide range of properties beneficial to various applications. In this review, we discussed numerous factors affecting the morphology and growth of nanostructures in electrodes, such as choices for precursors (salts, co-precursors, and solvents), reaction parameters (concentration, time, temperature, pressure, and pH), type of synthesis (bulk, templated, directly grown on current collectors) and structural changes after post-treatment and post-cycling. This review will help researchers to find the responsible factors related to the growth of nanostructures that can be easily engineered and controlled. Lastly, future outlooks and sustainable approaches in synthesizing nanostructured composites not only in energy storage but also in other applications are advocated for future developments. Graphical abstract: Image 1 Highlights: The relationship between the synthesis approaches and obtained nanostructures. Choices for precursors, reaction parameter, type of synthesis, and structural changes after post-treatment. Factors affecting the morphology of nanomaterials. Outlooks and future directions have been discussed.